First attempts in cylinder expansion testing - Künzel, Martin; Šelešovský, Jakub; Pachman, Jiří (Univerzita Pardubice, 2017)
The paper deals with cylinder expansion testing of sensitized nitromethane (PLX) confined in copper and aluminium tubes. The experiments were instrumented with Photonic Doppler velocimetry (PDV) and high speed framing camera to track expansion of the tubes. The PDV velocity-time records of the cylinder wall were converted to displacement-time profiles and then a fitting procedure was employed to find pressure-volume dependence of the expanding detonation products. The results compare to those obtained using Explo5 thermochemical code as well as to the literature data. An average Gurney velocity value of 2344 ± 40 m·s-1 was found. The results obtained with aluminium tubes were slightly lower than those with copper tubes. High speed photographs showed that there was no premature breakage of the tubes, although common materials were used.
Počáteční pokusy s cylindr testem
Keywords: cylinder expansion test; photonic Doppler velocimetry; PLX; nitromethane; cylindr test; PDV; PLX; nitrometan